Can the Spanish influenza pandemic of 1918 explain the baby-boom of 1920 in neutral Norway? - Svenn-Erik Mamelund (University of Oslo, Department of Economics, 2003)
The main purpose of this paper is to test the hypothesis that Spanish Influenza is the explanation of the dramatic fertility decline in Norway, from 1918 to 1919, and the subsequent baby-boom in 1920. The European country analyzed was not randomly picked; a neutral haven was chosen to possibly rule out the other, and probably more obvious candidate explaining the baby-boom of 1920; the First World War. The data used in the analysis are, in a European context, of superior quality as registration of population data including vital statistics continued as normal in Norway because the First World War did not disturb it. The paper also draws attention to the importance of including – in epidemic crisis models – not only mortality but also fear of contracting a coming or present epidemic – as well present epidemic disease experience – to explain why conception rates may fall in connection with an epidemic.
Keywords: J13; 330; Influenza; epidemic; fertility; Bevölkerungswachstum; Krankheit; Norwegen